2017
DOI: 10.1194/jlr.r075630
|View full text |Cite
|
Sign up to set email alerts
|

Cellular cholesterol homeostasis and Alzheimer's disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia in older adults. Currently, there is no cure for AD. The hallmark of AD is the accumulation of extracellular amyloid plaques composed of amyloid-β (Aβ) peptides (especially Aβ1-42) and neurofibrillary tangles, composed of hyperphosphorylated tau and accompanied by chronic neuroinflammation. Aβ peptides are derived from the amyloid precursor protein (APP). The oligomeric form of Aβ peptides is probably the most neurotoxic species; its accumulation eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 232 publications
(236 reference statements)
2
106
0
1
Order By: Relevance
“…It is characterized by intraneuronal neurofibrillary tangles (NFTs) containing highly phosphorylated tau and senile plaques composed of Aβ filaments, along with selective neuronal death in affected brain regions. Although the etiology of AD is unknown, it is believed that both environmental and genetic factors are involved among which disturbances in cholesterol metabolism have been implicated . Longitudinal studies revealed the positive correlation between higher blood concentration of total and low‐density lipoprotein cholesterol and faster global cognitive decline in late‐life .…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by intraneuronal neurofibrillary tangles (NFTs) containing highly phosphorylated tau and senile plaques composed of Aβ filaments, along with selective neuronal death in affected brain regions. Although the etiology of AD is unknown, it is believed that both environmental and genetic factors are involved among which disturbances in cholesterol metabolism have been implicated . Longitudinal studies revealed the positive correlation between higher blood concentration of total and low‐density lipoprotein cholesterol and faster global cognitive decline in late‐life .…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal cholesterol metabolism is an established feature of AD: levels of cholesterol are increased in MCI subjects and levels of 24-hydroxycholesterol and 27-hydroxycholesterol are elevated compared to controls both in AD and MCI subjects [24]. It appears that the rate of cholesterol production may be boosted by a free radical attack via a constitutive activation of HMGCoA-reductase, the rate-limiting step in sterol biosynthesis.…”
Section: Ad-associated Changes In Cholesterol Metabolismmentioning
confidence: 99%
“…This review focuses on discussing the connection between sterol metabolism and atherosclerosis as well as cancers. For a detailed discussion between cholesterol metabolism and neurodegenerative diseases, a recent review by Chang et al ( 201 ) is available. Detailed reviews on the roles of sterols in immune responses are available elsewhere ( 20 , 202 ).…”
Section: Sterols and Human Diseasesmentioning
confidence: 99%